Pengungkapan Diri Pengguna dan Berkenalan Melalui Aplikasi Tinder Di Surabaya - Elsada Rosanti Putri; Moch Djauhari; Moch Subechi Nurcahyo (LPPM Stikosa-AWS, 2022)
In social life, communication is a very important part of interacting with one or two people. Along with the development and advancement of information and communication technology supported by online media, therefore the role of online applications directly or indirectly has influenced every person or individual in self-disclosure and opening up space for interaction. Theories relevant to this research use interpersonal communication theory, CMC theory, and self-disclosure. This research was conducted using a qualitative method with a phenomenological approach. The subjects in this study were active Tinder users as many as 4 informants. Based on this research, it can be concluded that in using the Tinder application, each informant has different reasons. Each informant also has a different self-disclosure, for informant 1 it will be open if it has the same match as him. Informants 2 and 3 are not easy to open up to new people, and will open up if they know them longer and the other person opens up first. For the 4th informant, he is a person who is very open to new people.